POST-OPERATIVE PROTOCOL FOR BRAIN TUMOR SURGERY IN INTENSIVE CARE UNIT: A LITERATURE REVIEW - Kusumawardani, Dwi Indriati; Adiyanto, Bowo (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Brain tumors represent a diverse group of neoplasms arising from intracranial tissues, posing significant clinical challenges and impacting public health globally. With primary brain tumors having an annual incidence of around 14 per 100,000 individuals and secondary brain tumors being even more prevalent, the burden on healthcare systems is substantial. Postoperative care, particularly in the intensive care unit (ICU), plays a crucial role in monitoring patients for early detection of complications and maintaining neurological and systemic homeostasis. This study aims to serve a literature review to examine post operative management in brain surgery operation in the ICU in literatures. Result and Discussion: Protocols for ICU management post-brain tumor surgery are essential, with factors such as patient status, surgical site, and anticipated postoperative needs guiding decisions regarding ICU admission and monitoring. Neuroprotective strategies encompass physiological and pharmacological interventions aimed at mitigating adverse outcomes, with a multifaceted approach necessary for optimal neuroprotection. Conclusion: A comprehensive understanding of the surgical and postoperative management of brain tumors along with the implementation of evidence-based protocols for ICU care are essential to improve patient outcomes and minimize complications. Continued advancements in surgical techniques, neuroprotective strategies, and critical care management are crucial in addressing the complex challenges posed by brain tumors and enhancing the quality of care for affected patients.